CHILDREN AND POOR CITY IN MEDAN - Ruslan, Dede; Bahar, Andi; Pasaribu, Mangatas (Journal of Community Research and Service, 2018)
AbstractIbM program activities are aimed to help street children and poor cities that are assisted by SKA and PKPA in developing skill-based life skills education. Operationally this activity aims to help street children and urban poor in production. Types of production that have been done, among others, make various handicrafts from beads and acrylic, and packaging products Marginal Industry House. Methods of activities in the form of training and mentoring in production practices, packaging design practices, business management training and practice of machine use. Targets that have been implemented from IbM activities are: 1) The existence of various products of beads and acrylics, 2) The existence of cutting tools of sweet potatoes and bananas, 3) The existence of RIM'S design that attract and support the product selling value, 4) withdraw from each product and 5) The existence of simple bookkeeping and financial statements.Keywords: Street Children and Poor City, Multifarious Crafts, Cassava and Banana Cutting Tools, Packaging Design